2011
DOI: 10.1080/02603594.2011.618854
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic, Structural, and Physical Aspects of Organo-Oligogermanes

Abstract: The hydrogermolysis reaction has been used to prepare a variety of linear and branched oligogermanes that have been fully characterized. The combination of a germanium hydride protection= deprotection strategy with the hydrogermolysis reaction allows for the addition of one or two germanium atoms to the Ge -Ge chain at a time in linear systems, or three germanium atoms at a time in the case of branched systems. The physical properties of both types of oligogermanes have been probed using UV=visible spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…Oligogermanes are a class of catenated compounds that structurally resemble saturated hydrocarbons but possess physical properties that more closely mirror those of conjugated unsaturated polyenes. However, as opposed to these π-conjugated organic systems, oligogermanes exhibit σ-delocalization, where the pair of electrons present in the highest occupied molecular orbital (HOMO) are delocalized across the germanium–germanium backbone, provided that the germanium atoms are coplanar and are arranged in a sequential trans -conformation. , Therefore, these molecules can exhibit σ → σ* electronic transitions that are similar to the π → π* transitions observed in their doubly or triply bonded carbon congeners, resulting in the observation of broad but distinct absorbance peaks in their UV/visible spectra. The σ-bonding electrons present in these molecules have also been shown to interact with the available π or π* molecular orbitals on aryl substituents attached to the Ge–Ge backbone, which shifts their observed λ max values to lower energy. Oligogermanes are also electrochemically active, and their oxidation potentials can be readily obtained using cyclic voltammetry or differential pulse voltammetry. The majority of these compounds exhibit a single irreversible oxidation wave, although aryl-substituted linear oligogermanes have been shown to undergo n – 1 sequential oxidation steps, where n is the number of catenated germanium atoms. , …”
Section: Introductionmentioning
confidence: 99%
“…Oligogermanes are a class of catenated compounds that structurally resemble saturated hydrocarbons but possess physical properties that more closely mirror those of conjugated unsaturated polyenes. However, as opposed to these π-conjugated organic systems, oligogermanes exhibit σ-delocalization, where the pair of electrons present in the highest occupied molecular orbital (HOMO) are delocalized across the germanium–germanium backbone, provided that the germanium atoms are coplanar and are arranged in a sequential trans -conformation. , Therefore, these molecules can exhibit σ → σ* electronic transitions that are similar to the π → π* transitions observed in their doubly or triply bonded carbon congeners, resulting in the observation of broad but distinct absorbance peaks in their UV/visible spectra. The σ-bonding electrons present in these molecules have also been shown to interact with the available π or π* molecular orbitals on aryl substituents attached to the Ge–Ge backbone, which shifts their observed λ max values to lower energy. Oligogermanes are also electrochemically active, and their oxidation potentials can be readily obtained using cyclic voltammetry or differential pulse voltammetry. The majority of these compounds exhibit a single irreversible oxidation wave, although aryl-substituted linear oligogermanes have been shown to undergo n – 1 sequential oxidation steps, where n is the number of catenated germanium atoms. , …”
Section: Introductionmentioning
confidence: 99%
“…As part of our extensive investigations on the chemistry of discrete oligogermanes [13][14][15][81][82][83][84][85][86][87][88][89], we recently reported an investigation of the 73 Ge NMR spectra of several oligogermanes [13], which furthers the studies conducted by Wilkins et al [2] and Thomson et al [11]. The data from these three studies are shown in Table 9.…”
Section: Ge Nmr Spectra Of Oligogermanesmentioning
confidence: 74%
“…Oligogermanes are catenated compounds of germanium that can be regarded as the germanium analogues of hydrocarbons. These species are of interest due to their inherent σ-delocalization that results from the overlap of the diffuse 4sp 3 orbitals of the germanium atoms. The degree of σ-delocalization in these molecules is tunable and depends on the number of catenated germanium atoms and/or the electron-donating or -withdrawing nature of the organic substituents attached to the germanium–germanium backbone. The amount of σ-delocalization is also dependent on the conformation of the molecule, which is also influenced by the substituents and is maximized when a trans -coplanar arrangement of the atoms is present. , The position of the absorbance maximum for these oligogermanes undergoes a red shift, and the molecules become easier to oxidize as the chain length is increased or when more inductively donating organic substituents are attached to the chain.…”
Section: Introductionmentioning
confidence: 96%